CONTRACEPTIVE USE AMONG NEW ACCEPTORS IN JAVA ISLAND BEFORE AND DURING COVID-19 PANDEMIC - Mardhiyah, Nurifa Marwa (HIGEIA (Journal of Public Health Research and Development), 2023)
Abstract According to UNFPA, more than 47 million women could not access contraception during the COVID-19 pandemic. In Indonesia, family planning services during the COVID-19 pandemic showed a decrease in the number of contraceptives use by 40%. This study presents a comparison of contraceptive use among new acceptors on Java Island before and during the COVID-19 pandemic. This study used secondary data obtained from routine statistics of the national family planning program. This study is an analytical-descriptive study with an ecological design. The population in this study were all new contraceptive acceptors on Java Island in 2018–2021. Univariate and bivariate analysis were carried out. The results of this study found that there was a significant change in the number of new acceptors in DKI Jakarta (p=<0.001), Central Java (p=<0.001), DI Yogyakarta (p=0.001), East Java (p=0.005), and Banten (p=<0.001). Significant decrease occurred in most contraceptive methods, namely IUD (p=0.001), tubectomy (p=<0.001), vasectomy (p=<0.001), and injectable (p=0.022). This study indicates that there was a significant decrease in the new acceptor numbers during the pandemic on Java Island. Abstrak Menurut UNFPA, lebih dari 47 juta perempuan tidak dapat mengakses pelayanan kontrasepsi selama pandemi COVID-19. Di Indonesia, pelayanan KB pada masa pandemi COVID-19 menunjukkan penurunan jumlah penggunaan alat kontrasepsi sebesar 40%. Studi ini menyajikan perbandingan penggunaan kontrasepsi pada akseptor baru di Pulau Jawa sebelum dan selama pandemi COVID-19. Penelitian ini menggunakan data sekunder yang diperoleh dari statistik rutin program KB nasional. Penelitian ini merupakan penelitian deskriptif analitik dengan desain ekologi. Populasi dalam penelitian ini adalah seluruh akseptor baru di Pulau Jawa tahun 2018–2021. Teknik analisis univariat dan bivariat dilakukan. Hasil penelitian ini menunjukkan bahwa terjadi perubahan jumlah akseptor baru yang signifikan di DKI Jakarta (p=<0,001), Jawa Tengah (p=<0,001), DI Yogyakarta (p=0,001), Jawa Timur (p=0,005), dan Banten (p=<0,001). Penurunan signifikan terjadi pada sebagian besar metode kontrasepsi, yaitu IUD (p=0,001), tubektomi (p=<0,001), vasektomi (p=<0,001), dan suntik (p=0,022). Penelitian ini menunjukkan bahwa terjadi penurunan jumlah akseptor baru yang signifikan selama pandemi di Pulau Jawa.